2017
DOI: 10.4103/0971-4065.194394
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related acute kidney injury: An analysis of 165 cases

Abstract: Pregnancy-related acute kidney injury (PRAKI) contributes to 3–7% of overall acute kidney injury (AKI) cases in Indian subcontinent. The aim of this study was to determine the outcomes of PRAKI and risk factors associated with renal injury and maternal mortality. One hundred and sixty-five patients with PRAKI, seen at M. S. Ramaiah Medical College between 2005 and 2014, were included in this, observational study. AKI was analyzed in terms of maximal stage of renal injury attained as per Risk, Injury, Failure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 25 publications
3
47
5
1
Order By: Relevance
“…According to this study the common causes of pregnancy related AKI were Sepsis (59%), pre-eclampsia, and eclampsia (56%). 6 Huang C et al reported 0.81% incidence of AKI during pregnancy with about 17% women with pre-eclampsia/eclampsia and 60% women with HELLP syndrome developing AKI. 7 Another study done in Canada over a period of 15 years concluded that AKI is a rare complication of pregnancy.…”
Section: Resultmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this study the common causes of pregnancy related AKI were Sepsis (59%), pre-eclampsia, and eclampsia (56%). 6 Huang C et al reported 0.81% incidence of AKI during pregnancy with about 17% women with pre-eclampsia/eclampsia and 60% women with HELLP syndrome developing AKI. 7 Another study done in Canada over a period of 15 years concluded that AKI is a rare complication of pregnancy.…”
Section: Resultmentioning
confidence: 99%
“…One study showed Maternal and fetal mortality were 20% and 22% respectively and sepsis was the leading cause of maternal mortality. 6 Mortality rate may be as high as 58%, when associated with pancreatistis. 9 However, as we have a limited number of cases with pregnancy and pancreatitis associated AKI we are unable to make a conclusion on these findings.…”
Section: Resultmentioning
confidence: 99%
“…12 The lesser incidence of this problem is due to the improvement in antenatal care and the reduction of septic abortion due to its legalisation. 1,13,14 Socioeconomic factors contributing to PRAKI in the developing countries are mainly due to poverty, poor obstetrics care, lack of proper healthcare facilities and awareness of the condition, delayed referral process, multiparity, and the increasing population number. 15 Some studies summarized that the incidence of PRAKI was 1.0% to 2.8% in developed nations versus 4%-26% in developing countries.…”
Section: Incidencementioning
confidence: 99%
“…15 Some studies summarized that the incidence of PRAKI was 1.0% to 2.8% in developed nations versus 4%-26% in developing countries. 1,2,[12][13][14][15] A study from India revealed a decrease in PRAKI incidence from 22% between 1965 and 1974 to 9% between 1981 and 1986,which was the result of better obstetrical care and increased availability of medical facilities. 16 Definitions and criteria RIFLE: Increase in SCr X 1.5 or GFR decrease >25%.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation